PRESERVASI KURATIF ARSIP BERBAHAN DASAR KERTAS : STUDI KASUS TENTANG KEGIATAN RESTORASI (PRESERVASI KURATIF) ARSIP KONVENSIONAL DENGAN METODE MANUAL SYSTEM DI ARSIP NASIONAL REPUBLIK INDONESIA - Cecep Ibrahim (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2017)
This study dscusses curative preservation of paper-based archives; focusing on how curative preservation activities begin from preparation, implementation, to evaluation. The studyis focused on the restoration of conventional archives with manual system method in National Archives of Indonesia. The methodology used was case study. The study started from observation, continued with in-depth interview at National Archives of Indonesia. The results of the study were divided into three parts: preparation of conventional archive restoration activities, implementation of conventional archive restoration activities and evaluation of conventional archive restoration activities. The preparation of conventional archive restoration activities consists of preparation of tools and materials of archive restoration. The implementation of conventional archive restoration activities consists of numeration, recheck, cleaning, deacidification, lamination as archive repair using Japanese or local tissue paper, sizing using methyl cellulose, drying, astralon plastic release, cutting, pressing and reordering. The evaluation of conventional archive restoration activities controls the result of the archive restoration quality in the form of a ser es of tests on the archives both physically and chemically.